IMPACT OF SOCIAL MEDIA ON THE ACADEMIC PERFORMANCES OF ADVANCED LEVEL STUDENTS - Fawzan, Hasana Lebbe Mohamed (PUPIL: International Journal of Teaching, Education and Learning, 2020)
The research strives to understand the impact of social media engagement, its impact on the Advance Level student’s examination performance. It is an established fact that Social Media has a positive and negative impact on its youngsters. But social media is here to stay and will be a mainstream communication channel of mankind. The researcher reviewed the literature with authoritative sources to understand how Social Media impacts the education of the youth and to determine how the over-use of social media, has an impact on students’ academic performances particularly that of Advanced Level Students. The researcher used the Mixed Method Approach of Data Collection, Quantitative and qualitative information collection was undertaken. Data were collected from three groups, the advanced level students of Sri Lanka from Kurunegala District. Parents of such students participated in a face to face interview to collect rich information. Furthermore, a focus group discussion was carried out to collect information from Principals, Vice Principals, and sectional heads of schools in the Kurunegala District to test if there is a negative or positive impact on the advance level students' examination results if they indulge in social media engagement and networking.